Adoption and Effectiveness of Artificial Intelligence Applications in Improving Student Educational Performance: A Case Study of Badakhshan University, Afghanistan - Mohammadullah Shirpoor; Abdul Wajid Fazil; Assadullah Mohammadi (Gameology and Multimedia Expert, 2026)
The rapid advancement of artificial intelligence (AI) technologies has transformed educational practices worldwide; however, their adoption and effectiveness in developing countries, such as Afghanistan, remain limited. At Badakhshan University, students face challenges including limited digital literacy, infrastructural constraints, and uneven access to AI tools, which may hinder their academic performance. This study aims to examine the adoption of AI applications among students and evaluate their impact on educational outcomes. A quantitative case study was conducted involving 150 undergraduate students from four faculties: Computer Science, Economics, Education, and Agriculture. Data were collected using a structured questionnaire and analyzed through descriptive statistics. The findings reveal that most students possess moderate to high awareness of AI tools, with frequent usage reported for assignments, exam preparation, and concept clarification. AI applications were found to improve understanding of concepts, learning motivation, assignment completion, and overall academic performance. Challenges such as limited internet access, lack of technical skills, and insufficient institutional support were identified as barriers to effective adoption. In conclusion, AI technologies can significantly enhance learning outcomes at Badakhshan University, provided that infrastructural, technical, and training challenges are addressed. Strategic implementation of AI can foster equitable access and improve educational performance across faculties.